The impact of sodium chloride reduction on Grana-type cheese production and quality. Issue 4 (14th November 2019) - Tidona, Flavio; Bernardi, Marco; Francolino, Salvatore; Ghiglietti, Roberta; Hogenboom, Johannes A.; Locci, Francesco; Zambrini, Vittorio; Carminati, Domenico; Giraffa, Giorgio
Abstract: With the aim to reduce the Na content, hard cheeses manufactured using the same technology as for Grana cheese (Grana-type) were salted using three brines containing different amounts of KCl (K-brines) and compared with control cheeses, salted with marine NaCl. A lower weight loss was observed in cheeses salted with K-brines (K-cheeses), whereas the yield and dry matter did not differ significantly between K-cheeses and controls. After 3 months of ripening ( T 3 ), the distribution of the Na cations (Na) was centripetal, with a higher Na concentration in the outer (0–3 cm of depth) layer, whereas the K cations (K) seemed to diffuse into the cheese more rapidly and homogeneously. Starting from the 6th month ( T 6 ), the distribution of both Na and K was stabilized through the different cheese layers. The use of the brine with the highest concentration of potassium (53.8% K) enabled us to successfully halve the Na content compared to the controls whereas, with the other brines, the reduction of Na was below 30%. At the end of ripening ( T 9 ), all the cheeses were without defects and the partial substitution of Na with K did not impact on the chemical composition, microbiological characteristics and ripening process. The sensory evaluation did not show any difference between K-salted and control cheeses in discriminant analysis.